Environmental and economic assessment of borehole thermal energy storage in district heating systems. (15th April 2018) - Welsch, Bastian; Göllner-Völker, Laura; Schulte, Daniel O.; Bär, Kristian; Sass, Ingo; Schebek, Liselotte
Graphical abstract: Highlights: Economic and environmental LCA of medium deep BTES in DH generation is carried out. Various system compositions and changing boundary conditions are investigated. Pareto fronts illustrate optimal system designs with and without BTES. Economic and environmental assumptions affect optimal system designs considerably. Combinations of BTES, solar heat & a small CHP are competitive with CHP-based systems. Abstract: District heating will play an important role for heat provision in temperate and cold climate zones in the future. However, in the context of decarbonizing the heating sector, conventional heat sources have to be replaced by renewable energies. This replacement correlates to the necessity to integrate the fluctuating energy source of solar radiation and thus requires seasonal thermal energy storage. More recently, borehole thermal energy storage systems have been integrated into such district heating concepts. Yet, the potential greenhouse gas emission reduction and the financial benefits of these innovative district heating concepts have not been assessed with respect to the environmental burden and the associated investment cost of the modernization. This study presents a comprehensive environmental and economic life cycle assessment of a fictional district heating system with varying shares of shallow to medium deep borehole thermal energy storage and alternative heat sources replacing conventional capacity. In an exemplary district heating system covering 25 GW h of annual heat demand, borehole thermal energy storage can decrease the greenhouse gas emissions of combined heat and power plants and solar thermal collectors by over 40%. Boundary conditions assumed for the development of the energy market and the existence of subsidies have a significant impact on the emission savings and the levelized cost of heat. Considering a probable increase of energy costs and a growing share of renewables in the electricity mix, a combination of solar thermal collectors and borehole thermal energy storage with a small heat and power plant is the best solution, which is economical even without subsidies. The results of the study promote the construction of medium deep borehole thermal energy storage systems that can help to increase the share of renewable energy in the heating sector at reasonable cost.